RADIO FREQUENCY IDENTIFICATION (RFID) AND EASE OF LIFE - Jituri, Vishwajeet V. (International Journal of Research -GRANTHAALAYAH, 2020)
The usage of RFID technology is rapidly increasing. The RFID system provides distinct advantages over the traditional barcode system. The RFID technology is being used in many areas like toll collection, shopping and retail, agriculture, transportation, industries, academics etc. There are some limitations also with the RFID technology including the privacy issues. This paper describes some of the RFID uses which result in ease of life.